A CONTRIBUTION TO THE STUDY OF THERMAL LOADS OF HYDRAULIC AND ACTIVE MOUNTS OF POWERTRAIN OF A FREIGHT MOTOR VEHICLE - Demić, Miroslav; Diligenski, Đorđe Mihailo (Journal of Applied Engineering Science, 2018)
Due to the excitation from the road micro unevenness, powertrain vibration and conditions of motion (acceleration, braking, curved motion) trucks masses make complex spatial oscillatory movements. The negative impact of these movements, i.e. dynamic loads arising from those movements and transferred to the vehicle chassis, can be reduced by the proper choice of the position and characteristics of the powertrain mounts. The elastodamping forces in the mounts perform mechanical work which is converted into a thermal energy. Theoretical, experimental and combined methods can be used to analyse thermal loads of mounts. In this paper, research was carried out using theoretical methods using the simplified mechanical model of the powertrain. The vibrations of the powertrain of a trucks manufactured by FAP were observed. Thermal load analysis was performed for hydraulic and active mounts.